2015
DOI: 10.1002/jcb.25153
|View full text |Cite
|
Sign up to set email alerts
|

Gcn5 Modulates the Cellular Response to Oxidative Stress and Histone Deacetylase Inhibition

Abstract: To identify chemical genetic interactions underlying the mechanism of action of histone deacetylase inhibitors (HDACi) a yeast deletion library was screened for hypersensitive deletion mutants that confer increased sensitivity to the HDACi, CG-1521. The screen demonstrated that loss of GCN5 or deletion of components of the Gcn5 histone acetyltransferase (HAT) complex, SAGA, sensitizes yeast to CG-1521-induced cell death. Expression profiling after CG-1521 treatment reveals increased expression of genes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
(39 reference statements)
2
18
0
Order By: Relevance
“…Lysine acetylation is a reversible process catalyzed by acetyltransferases and deacetylases (9). To identify the acetyltransferase responsible for TyrRS acetylation, we overexpressed p300/CBP-associated factor (PCAF), Tip60, and GCN5 into HEK293T cells, because PCAF, Tip60, and GCN5 have been shown to respond to oxidative stress (22)(23)(24)(25), and found that the acetylation of TyrRS was elevated only after the ectopic expression of PCAF, not the other acetyltransferases ( Fig. 2A).…”
Section: Significancementioning
confidence: 99%
“…Lysine acetylation is a reversible process catalyzed by acetyltransferases and deacetylases (9). To identify the acetyltransferase responsible for TyrRS acetylation, we overexpressed p300/CBP-associated factor (PCAF), Tip60, and GCN5 into HEK293T cells, because PCAF, Tip60, and GCN5 have been shown to respond to oxidative stress (22)(23)(24)(25), and found that the acetylation of TyrRS was elevated only after the ectopic expression of PCAF, not the other acetyltransferases ( Fig. 2A).…”
Section: Significancementioning
confidence: 99%
“…However, we cannot exclude the possibility that complexes other than SAGA, such as the SAGA-like complex (27,38), components of which are shared with SAGA, mediate transcriptional regulation of dcl2. Roles of the SAGA complex in abiotic stress responses have been extensively studied in other organisms, particularly in yeast (34,39,40), but rarely in biotic stress conditions, including virus infection. This is an example of SAGA's involvement in an antiviral response.…”
Section: Saga Mediates Virus-responsive Induction Of Rnai Key Genesmentioning
confidence: 99%
“…The results demonstrate that UTI can effectively prevent liver injury, reduce proinflammatory cytokines, relieve oxidative stress, and strengthen the antioxidant defense system. Oxidative stress can activate molecular pathways that provoke inflammation and directly cause tissue damage . This type of tissue injury is considered as one of the most important mechanisms in the progression of multiple organ failure due to septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can activate molecular pathways that provoke inflammation and directly cause tissue damage. 21 This type of tissue injury is considered as one of the most important mechanisms in the progression of multiple organ failure due to septic shock. Our data showed that the changes in serum liver function parameters can reflect the pathological changes of the liver.…”
Section: Discussionmentioning
confidence: 99%